iOS application for occupational therapist - Quek, Desmond Shu Wei (2015)
In recent years, the mobile application market has seen exponential growth, with app stores providing myriad categories of applications. However, the market seems to fall short of applications that allow occupational therapists to prescribe personalized prescriptions, and facilitate interaction between occupational therapists and patients. This project aims to serve as a bridge between both occupational therapists and their patients. It allows occupational therapists to prescribe personalized prescription for their patients. It also allows both patients and occupational therapists to monitor the former’s injuries of past and present. Occupational therapists play a specialized role in the department of rehabilitation. The primary purpose of occupational therapy is to explicate and maintain a person’s capacity, so as to ensure they are able to reach a desired level of functionality. This includes the ability to perform day-to-day roles, personal care and hygiene, daily living, and tasks required by their job. By diagnosing and analyzing the patient’s injury or condition physically, the occupation therapist is able to better prescribe personalized exercises to suit the patient’s condition. The project was completed in the final academic year. The student has successfully completed the project with a working product with the abovementioned rationale. It was a memorable and fruitful process of research and self-learning that equipped the student from knowing little about iOS programming to a novice. The knowledge gained was mainly in the department of developing iOS applications for iPhones and iPads, as well as the domain area of healthcare occupational therapy.